Social Assistance to Families and Children of the Volga Region Resettled to the Smolensk Province in 1921–1923 - Natalia Mitsyuk (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The achievements and failures of the Soviet government aimed at combating Volga region famine in 1921–1922 had an impact on social policy in the first decade of the Soviet state. The study of the experience of social policy in relation to families and children evacuated from the Volga region is becoming especially relevant in modern conditions of searching for effective forms of social assistance to families trapped in areas of natural disasters and military conflicts. Methods and materials. The publication is based on numerous archival records, which contain documents on the organization of social work with families and children of the Volga region, resettled in 1921–1923 in the Smolensk province. The key methods were source analysis, methods of everyday history, and microhistory. The documents of the funds of the provincial and district commissions for helping the starving in the Volga region and the provincial and district health departments of the State Archives of the Smolensk region were studied. Analysis. The Сentrally developed plan for the evacuation of refugees went out of control in the first months due to a lack of local funds and an uncontrolled flow of refugees. The main efforts in the region were thrown at the organization of social work with evacuated children. Working with arriving children has become a serious test for local authorities. All financial costs for the maintenance of refugees fell on the region. The number of children who arrived in the province exceeded the planned values by more than 2 times. For the first time in the region, a new model of charity was tested, which consisted of the mass and mandatory participation of all groups of the population and foreign organizations. The main methods of working with children were placing them in specialized orphanages, opening sectoral orphanages, insulators and distributors, and placing children in foster families. The forced abandonment of children by refugee parents in order to save them from starvation has become widespread. Temporary delivery of children to peasant families for agricultural work was practiced. Bureaucratic mistakes, interdepartmental inconsistency, and local negligence led to poor provision of children with food, clothing, and medical care. Indirect data indicate high infant mortality. Many children remained in shelters in Smolensk and were not re-evacuated. Results. The archival material of the Smolensk region showed the difficulties of practical implementation of the plan of assistance to resettled families developed by the central authorities, the need for a flexible approach on the ground, and taking into account regional specifics.